Breaking and Making of Carbon–Carbon Bonds by Lanthanides and Third‐Row Transition Metals. Issue 9 (27th January 2016) - Zhou, Shaodong; Li, Jilai; Schlangen, Maria; Schwarz, Helmut
Abstract: Carbon‐atom extrusion from the ipso ‐position of a halobenzene ring (C6 H5 X; X=F, Cl, Br, I) and its coupling with a methylene ligand to produce acetylene is not confined to [LaCH2 ] + ; also, the third‐row transition‐metal complexes [MCH2 ] +, M=Hf, Ta, W, Re, and Os, bring about this unusual transformation. However, substrates with substituents X=CN, NO2, OCH3, and CF3 are either not reactive at all or give rise to different products when reacted with [LaCH2 ] + . In the thermal gas‐phase processes of atomic Ln + with C7 H7 Cl substrates, only those lanthanides with a promotion energy small enough to attain a 4f n 5d 1 6s 1 configuration are reactive and form both [LnCl] + and [LnC5 H5 Cl] + . Branching ratios and the reaction efficiencies of the various processes seem to correlate with molecular properties, like the bond‐dissociation energies of the C−X or M + −X bonds or the promotion energies of lanthanides. Abstract : Make or break ! The experimental scope and limitations of the carbon‐atom extrusion from halobenzenes and its coupling with the methylene ligand of [LaCH2 ] + to form acetylene under ambient conditions is reported. With regard to the nature of the metal it has been shown that also the third‐row transition‐metal carbenes [M(CH2 )] + (M=Hf, Ta, W, Re, and Os) are capable to bring about efficient C2 H2 formation in their reactions with C6 H5 Cl.